2011
DOI: 10.1111/j.1745-4557.2011.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

1-Methylcyclopropene Delays Postharvest Ripening and Reduces Decay in Hami Melon

Abstract: The effects of 1-methylcyclopropene (1-MCP) on postharvest ripening and fruit decay in Hami melon were investigated. Melons were treated with 0, 0.1, 1, or 5 mL/L 1-MCP at 25C for 24 h and then stored at 25C for 16 days. 1-MCP treatment significantly inhibited respiration rate and ethylene production and delayed their climacteric rise. The treatment also significantly inhibited the decrease of firmness and the increase of electrolyte leakage. Moreover, treatment with 1 or 5 mL/L 1-MCP maintained significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
5
1
Order By: Relevance
“…1-MCP was effective in postharvest storage of melon (de Melo et al., 2008; Gal et al., 2006; Li et al., 2011b) although inconsistent results were obtained on the most effective concentration of 1-MCP in these reports. As for commercial usage, it is important to establish the optimum 1-MCP dose to achieve the maximum efficiency.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…1-MCP was effective in postharvest storage of melon (de Melo et al., 2008; Gal et al., 2006; Li et al., 2011b) although inconsistent results were obtained on the most effective concentration of 1-MCP in these reports. As for commercial usage, it is important to establish the optimum 1-MCP dose to achieve the maximum efficiency.…”
Section: Introductionmentioning
confidence: 95%
“…Several research were reported about the effect of 1-MCP application on melons. In ‘Galia’ melon (Ergun et al., 2005; Gal et al., 2006) and ‘Hami’ melon (Bi et al., 2003; Li et al., 2011a, 2011b), it is found that 1-MCP significantly extended melon shelf life, improved external qualities and nutritional qualities of melon fruits. And 1-MCP is also proved to be effective in improving fruit qualities of cantaloupe (Amaro et al., 2013) and ‘Yujinxiang’ melon (Ma et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is very popular for its bright skin colour, crispy, juicy flesh texture and delicious flavour (Bi et al ., ; Cong et al ., ). Every year when hami melons are in season, many hami melons rot in the farmland because of long distance to transport them from Xinjiang to the eastern and southern provinces of China (Li et al ., ) and lack of effective deep‐processing in their producing area (Ma et al ., ), which finally causes serious economic losses (Bi et al ., ). So it is crucial to find effective and proper processing technologies to promote the development of hami melon industry.…”
Section: Introductionmentioning
confidence: 99%
“…The mRNA transcript levels of both genes showed significant increases during ripening in storage, possibly resulting from the increase in ethylene production of melon fruit. Although we did not measure the ethylene production of melon fruit during storage, increases in ethylene production during ripening have been reported for different melon cultivars (Ergun et al, 2005;Pech et al, 2008;Li et al, 2011). Moreover, it has been reported that there was a correlation between the increase in ethylene production and the increase in the transcript levels of ETR1 and ETR2 genes in cucumber and melon (Sato-Nara et al, 1999;Yamasaki et al, 2000;Cin et al, 2006).…”
Section: Discussionmentioning
confidence: 87%